EPIDEMIOLOGICAL RISK FACTORS FOR THE OCCURRENCE OF IRON DEFICIENCY IN CHILDREN AND ADOLESCENTS OF THE KRASNODAR TERRITORY - V. A. Shashel; A. A. Bishenova; E. G. Potyagailo; N. N. Shchegolevataya (Кубанский научный медицинский вестник)
Aim. The study is to establish causally significant epidemiological risk factors for the occurrence of iron deficiency disorders (WDS) in children and adolescents in the Krasnodar Territory.Materials and methods. The absolute and relative risks of the formation of GVD in 605 children and adolescents aged from birth to 18 years, living in the territories of the Krasnodar Territory with various ecological conditions, were studied. The ecological situation in the province was assessed according to the method previously proposed by V.A. Shashel et al. (2000). The following characteristics of the general blood test performed on an automatic analyzer with the determination of hemoglobin (Hb), the number of red blood cells (RBC), hematocrit (Ht), erythrocyte indices (mean erythrocyte volume- MCHC, width of red blood cell distribution by volume-RDW, reflecting The degree of anisocytosis), the number of reticulocytes (Ret), and the hemoglobin content in the reticulocytes (CHr). The serum iron (SJ), serum ferritin (SF) and total iron binding capacity of serum (BFW) were determined. The saturation coefficient of ferric iron was calculated by the formula: NTZ=SZ/OZSS.100%. The relative risk (RR) was calculated using the formula: R=d.a/b.c.Results. The study of the influence of various endogenous and exogenous epidemiological risk factors on the occurrence of GVD in children allowed the identification of 25 most significant factors. Of the medical and biological antenatal and intranatal reasons, the main ones were placental insufficiency, multiple pregnancy, diseases of pregnant women, including anemia. Of the postnatal factors, the leading ones were insufficient intake of iron with food in the form of early artificial feeding, the use of unadapted milk mixtures of cow or goat milk. Increased need for iron occurs in children with accelerated growth rates in early, prepubertal and pubertal age, and increased losses of this macroelement were due to intestinal absorption, bleeding of various etiologies, including a part of girls during the period of menstrual cycle. The main risk factors for social and hygienic reasons can be attributed to an unbalanced diet with a rare intake of meat products, a strict vegetarian, flour, milk, sweet rations, a rare intake of fruits and vegetables, leading to a qualitative and quantitative deficiency of macro- and micronutrients. The majority of children had a disturbance of the regime of the day and nutrition, the use of fast food, inactivity. The majority of these risk factors for the development of LVS have occurred in the upbringing of children by parents, smokers and mothers in families with low material incomes and low medical activity in the family. The detected risk factors for the emergence of GVH in children exacerbate its effect against the background of air pollutants, water basins and agricultural lands.Conclusion. The detected risk factors make it possible to form children in risk groups for the occurrence of their WDN, to timely appoint a diagnosis for diagnosis, treatment and develop targeted programs for primary prevention and rehabilitation of these diseases.